2017
DOI: 10.1038/s41598-017-00489-x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Dark-field Radiography - In-Vivo Diagnosis of Lung Cancer in Mice

Abstract: Accounting for about 1.5 million deaths annually, lung cancer is the prevailing cause of cancer deaths worldwide, mostly associated with long-term smoking effects. Numerous small-animal studies are performed currently in order to better understand the pathogenesis of the disease and to develop treatment strategies. Within this letter, we propose to exploit X-ray dark-field imaging as a novel diagnostic tool for the detection of lung cancer on projection radiographs. Here, we demonstrate in living mice bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 47 publications
(51 reference statements)
1
54
0
Order By: Relevance
“…This observation is supported by the aforementioned recent study investigating dark-field imaging in a mouse model of neonatal lung injury due to mechanical ventilation and supplementation of oxygen-enriched gas [ 18 ]. Additionally, in a mouse model of lung cancer, regions with cancerous tissue show a reduced air:tissue volume ratio due to uncontrolled cell proliferation and loss of alveolar space and therefore X-ray scattering is strongly reduced [ 30 ]. Based on previous publications in small-animal models, it is unlikely that the overall conclusions of our study are compromised by the fact that imaging was performed on a dead human body rather than living subject.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is supported by the aforementioned recent study investigating dark-field imaging in a mouse model of neonatal lung injury due to mechanical ventilation and supplementation of oxygen-enriched gas [ 18 ]. Additionally, in a mouse model of lung cancer, regions with cancerous tissue show a reduced air:tissue volume ratio due to uncontrolled cell proliferation and loss of alveolar space and therefore X-ray scattering is strongly reduced [ 30 ]. Based on previous publications in small-animal models, it is unlikely that the overall conclusions of our study are compromised by the fact that imaging was performed on a dead human body rather than living subject.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on pulmonary diseases in mouse models have demonstrated dark-field radiography of the lung to improve the diagnosis of pulmonary emphysema 1 3 , fibrosis 4 , bronchopulmonary dysplasia 5 , lung cancer 6 , and pneumothoraces 7 . Investigation of animal models with chest dimensions comparable to humans is an essential step toward the potential in vivo implementation of this new imaging modality in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…A dark-field signal is generated when sub-pixel structures scatter the x-ray wavefield, and the strength of this signal will depend on the number and size of scattering structures [21,22]. As a result of the many scattering structures in the lung the technique can provide high contrast lung images, provided the temporal resolution is not important [23,24,25,26,27], making some clinical applications feasible [28,29]. We considered if there was potential for the dark-field modality to reveal the presence of treatment, noting that the treatment delivery is not a repeated motion.…”
Section: Accepted Manuscriptmentioning
confidence: 99%